English Language Teaching Digital Module for Android-Based Food and Beverage Services - Ni Nyoman Nidya Trianingrum; Sulistyoadi Jokosaharjo; Ni Luh Putu Sri Widhiastuty (Universitas Pendidikan Ganesha, 2024)
The Covid-19 pandemic forced the schools to conduct e-learning. The challenges are even greater for vocational schools since the students do practices using specific instruments. Thus, this study aimed to develop an Android-based digital module for teaching English for food and beverage services to help students learn English effectively through online learning. This study followed the 4D model of research and development study. The data of the study were collected through observation, documentation, expert judgment, and questionnaire. The data were analysed both qualitatively and quantitatively. This study successfully developed the final format of the module in the form of an electronic book consisting of eight units. In addition, the quality of the module can be categorized as very good material based on the questionnaire results, which were given to the related students, lecturers, and expert judges. The exercises provided in the module provide many opportunities for students to practice and learn. The implication of this finding has a potential to revolutionize the way that English is taught and learned. By providing students with access to high quality digital modules can help students to achieve the student’s English language learning in Food and Beverage Services. This research merely evaluates the module in the formative process.